Resilience to global headwinds? CESEE responses to changing trade and financial landscape - focus on the Macedonian economy - Vesna Stojchevska (National Bank of the Republic of Macedonia, 2019)
This analysis is aimed at investigating the response of the CESEE economies, and especially of the Macedonian economy, to the changing global environment in the latest period, predominantly to the recent challenges coming from the global trade and financial landscape. It offers a historical overview of the trade and financial linkages between these countries and the EU, as well as the EU largest economy - Germany, with a further focus on the growing importance of the Global Value Chains for the trade integration between the CESEE region and Germany. More detailed perspective is given for the Macedonian economy, through the recent change in the trade and production structure, driven by the deeper integration into the GVCs in the last decade. Additionally, a short overview of the recent trade disputes between the US and China is given, focused on the potential adverse effect on the global and EU economy, as an increasing external risk for the prospects of the domestic economy and the region as a whole.
Keywords: 330; Internationale Wirtschaft; Wirkungsanalyse; Regionale Wirtschaftsintegration; Exportdiversifizierung; Betriebliche Wertschöpfung; Nordmazedonien; Osteuropa